Lipophilic properties of anti‐Alzheimer's agents determined by micellar electrokinetic chromatography and reversed‐phase thin‐layer chromatography. Issue 9 (15th March 2017) - Godyń, Justyna; Hebda, Michalina; Więckowska, Anna; Więckowski, Krzysztof; Malawska, Barbara; Bajda, Marek
Abstract : Lipophilicity as one of the most important physicochemical properties of the biologically active compounds is closely related to their pharmacokinetic parameters and therefore, it is taken into account at the design stage of new drugs. Among the novel, fast, and reliable methods for determination of the lipophilicity of compounds micellar electrokinetic chromatography (MEKC) is considered to be an appropriate one for bioactive molecules, as it closely mimics the physiological conditions. In this paper MEKC was used for the estimation of log P values for 49 derivatives of phthalimide, tetrahydroisochinoline and indole, designed and synthesized as potential anti‐Alzheimer's agents with cholinesterase inhibitory activity. RP‐TLC method was applied for determination of another lipophilicity descriptor ‐ RM0 . The results of both experimental methods were compared with each other giving satisfactory correlation ( R = 0.784), and with computational methods (Marvin, ChemOffice Software) resulting in weaker correlation ( R = 0.466–0.687). The lipophilicity–activity relationship was finally established, showing significant influence of lipophilicity on cholinesterase inhibition in some subgroups of phthalimide derivatives.